General characteristics of representative bodies of local self-government in the Republic of Kazakhstan and the Russian Federation - Ternovaya, N.S. (Bulletin of the Karaganda University “Law Series”, 2018)
In this article, the author conducts a comparative legal analysis of the system of local self-government in the two largest countries of the post-Soviet space - the Republic of Kazakhstan and the Russian Federation. Having many similarities and differences, local government systems have one common feature - the primacy of the representative body and its top priority in matters of local importance. Taking into account the conditions in which the system of local self-government developed in both countries, the author of the article, by means of a comparative legal method, determines the criteria that occupy the dominant position when taking into account the construction, organization, functioning and prospects for the development of the local government system through the prism of local representative bodies of the Russian Federation and the Republic Kazakhstan. The urgency of this issue has both scientific and practical significance for the purpose of increasing the effectiveness of the work of the representative body in the framework of local self-government.